MECHANISMS FOR CREATION OF DIDACTIC MATERIALS BASED ON A CREATIVE APPROACH (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This scientific and theoretical analytical article reveals opinions on the mechanisms of creating didactic support based on a creative approach.